Pollen niche of Melipona (Melikerria) interrupta (Apidae: Meliponini) bred in a meliponary in a terra-firme forest in the central Amazon - Ferreira, Marcos Gonçalves; Absy, Maria Lúcia (Palynology, 2018)
Monthly corbicular samples derived from weekly collections of Melipona (Melikerria) interrupta (Apidae: Meliponini) were analyzed alongside a single honey sample between January to December 2012. The botanical families Arecaceae, Melastomataceae and Solanaceae were the most representative in the corbicular load samples, with five temporary specialization events (>90%) being detected for representatives of Melastomataceae and Solanaceae. Furthermore, Melastomataceae also exhibited a greater contribution of pollen types in the honey samples, particularly because of the occurrence of Miconia type (87.17%), followed by Solanaceae, represented by types Solanum stramonifolium (5.00%) and Solanum aculeatissimum (2.50%). The low richness of pollen types in the corbicular pollen samples (n = 16) in this study suggests that M. interrupta may act as a specialist due to the low availability of apiculture resources in terra-firme environments, where intraspecific competition might affect not only the maintenance of these colonies in this environment but also their honey production. © 2017 AASP–The Palynological Society.
Keywords: Apiculture; Colony; Dicotyledon; Honeybee; Intraspecific Competition; Morphology; Pollen; Specialization; Species Richness; Amazonia; Apidae; Arecaceae; Melastomataceae; Melipona; Meliponinae; Miconia; Solanaceae; Solanum Aculeatissimum; Solanum Stramoniifolium